Exercise of social control in Brazilian's National Health System: nurses' point of view as a member of local health council - Martins, Amanda de Lucas Xavier; Santos, Sueli Maria dos Reis (Saúde e Sociedade, 2012)
The study tries and reveal nurses' point of view about their performance in Local Council of Health (CLS) in relation to the organizational principle of SUS of social control of the planning, monitoring and evaluation of the health unit's actions. A qualitative research of descriptive exploratory type was conducted; data were collected through interviews of nurses working at Basic Units of Health (UBS) of Juiz de Fora which were active in Local Council of Health. 15 nurses were interviewed, when saturation of data was reached. Analysis of data was made under two thought axes: the nurses' opinion in relation to their role as Local Counselor of Health, taking part in the social control of SUS' administration, and regarding the perceived reflexes of this participation at the health service (UBS) and over community health's conditions. RESULTS: most of the interviewees is aware of the importance of the CLS and consider Nurse's participation at CLS important, due to their training in aspects of social practice and in public health. However, many interviewees still believe that the Nurse's acting in CLS is important only as space to publicize primary care services' actions and needs.